Proteomic Signatures of Microbial Adaptation to the Highest Ultraviolet-Irradiation on Earth: Lessons From a Soil Actinobacterium - Zannier, Federico; Portero, Luciano R.; Douki, Thierry; Gärtner, Wolfgang; Farías, María E.; Albarracín, Virginia H. (Frontiers in Microbiology, 2022)
In the Central Andean region in South America, high-altitude ecosystems (3500-6000 masl) are distributed across Argentina, Chile, Bolivia and Peru, in which poly-extremophilic microbes thrive under extreme environmental conditions. In particular, in the Puna region, total solar irradiation and UV incidence are the highest on Earth, thus, restraining the physiology of individual microorganisms and the composition of microbial communities. UV-resistance of microbial strains thriving in High-Altitude Andean Lakes was demonstrated and their mechanisms were partially characterized by genomic analysis, biochemical and physiological assays. Then, the existence of a network of physiological and molecular mechanisms triggered by ultraviolet light exposure was hypothesized and called "UV-resistome". It includes some or all of the following subsystems: (i) UV sensing and effective response regulators, (ii) UV-avoidance and shielding strategies, (iii) damage tolerance and oxidative stress response, (iv) energy management and metabolic resetting, and (v) DNA damage repair. Genes involved in the described UV-resistome were recently described in the genome of Nesterenkonia sp. Act20, an actinobacterium which showed survival to high UV-B doses as well as efficient photorepairing capability. The aim of this work was to usea proteomic approach together with photoproduct measurements to help dissecting the molecular events involved in the adaptive response of a model High-Altitude Andean Lakes (HAAL)extremophilicactinobacterium,Nesterenkonia sp. Act20, under artificial UV-B radiation. Our results demonstrate that UV-B exposure induced over-abundance of awell-defined set of proteins while recovery treatments restored the proteomic profiles present before the UV-challenge. The proteins involved in this complex molecular network were categorized within the UV-resistome subsystems: damage tolerance and oxidative stress response, energy management and metabolic resetting, and DNA damage repair.